Respuesta :

Answer:

[tex]g(f(3))=-2[/tex]

Step-by-step explanation:

So we have the two functions:

[tex]g(x)=4x+2\text{ and } f(x)=3x-10[/tex]

And we want to find g(f(3)).

So, let's find f(3) first:

[tex]f(3)=3(3)-10[/tex]

Multiply:

[tex]f(3)=9-10[/tex]

Subtract:

[tex]f(3)=-1[/tex]

Therefore, we can substitute -1 for f(3):

[tex]g(f(3))=g(-1)[/tex]

Now, find g(-1):

[tex]g(-1)=4(-1)+2[/tex]

Multiply:

[tex]g(-1)=-4+2[/tex]

Add:

[tex]g(-1)=-2[/tex]

And we're done!

So:

[tex]g(f(3))=-2[/tex]